Barbie : the world tour - Robbie, Margot, 1990-; Mukamal, Andrew (Rizzoli, 2024)
For the press tour following the record-breaking release of Greta Gerwig's award-winning, acclaimed Barbie movie, producer and star Margot Robbie and her stylist Andrew Mukamal immersed themselves in some of Barbie's most iconic outfits and curated vintage pieces, then approached designers, from Giorgio Armani to Donatella Versace, to create looks inspired by the doll-size originals. Many of these looks were not seen as the official Barbie press tour was cut short--so Margot and Andrew worked with renowned fashion photographer Craig McDean to shoot her in the looks exactly as they were curated: Schiaparelli in Los Angeles, Vivienne Westwood in London, vintage Chanel with matching Steamline luggage at the airport, and beyond..